2000
DOI: 10.1159/000017225
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging and Histopathology in Dementia, Clinically of Frontotemporal Type

Abstract: The magnetic resonance imaging (MRI) and computed tomography findings in 28 patients with the clinical diagnosis of frontotemporal dementia (FTD) were compared with the findings in a control group of 76 individuals without dementia or stroke. A pattern of frontal and temporal atrophy with predominantly frontal white matter changes was found in the FTD patients, and this was significantly different from the radiological findings in the control group. Six of the FTD patients have undergone autopsy. Histopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…Diffuse increase in white matter signal intensity in the frontal and/or temporal lobes on MRI has been reported in patients with the clinical diagnosis of FTD [2]. In a previous study of 28 FTD patients compared with 76 normal controls, we found an MRI pattern with frontotemporal atrophy and predominantly frontal white matter changes in FTD, correlating with the histopathological findings at neuropathological examination, which was performed in 6 of these FTD patients [4].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Diffuse increase in white matter signal intensity in the frontal and/or temporal lobes on MRI has been reported in patients with the clinical diagnosis of FTD [2]. In a previous study of 28 FTD patients compared with 76 normal controls, we found an MRI pattern with frontotemporal atrophy and predominantly frontal white matter changes in FTD, correlating with the histopathological findings at neuropathological examination, which was performed in 6 of these FTD patients [4].…”
Section: Discussionsupporting
confidence: 60%
“…The histopathological white matter pathology has been shown to appear in at least two different forms, each of which associating differently with the microscopical grey matter changes [3,4]. The interpretation of white matter magnetic resonance imaging (MRI) changes may thus be difficult, and this may partly be due to additional pathologic alterations appearing in the interval between MRI and post-mortem histopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Besides pathology of the basal ganglia, white matter pathology is frequent, albeit underrecognized in FTD (Englund and Brun, 1987;Larsson et al, 2000;Larsson et al, 2004) and the present findings may indicate that white matter changes here influenced the early reported clinical symptoms. EEG has not been widely used in FTD, although a normal or near normal visual EEG has been considered as a criterion of a degenerative disorder of nonAlzheimer type (The Lund and Manchester Groups, 1994).…”
Section: Discussionmentioning
confidence: 51%
“…The visuospatial ability and praxis were preserved after 13 years of illness. CT and MRI showed bilateral temporal lobe atrophy and white matter changes in the frontal lobes [4,5]. Neuropathological data from the pedigree are unfortunately not available to date.…”
mentioning
confidence: 99%